2021
DOI: 10.1002/ehf2.13717
|View full text |Cite
|
Sign up to set email alerts
|

Aetiological classification and prognosis in patients with heart failure with preserved ejection fraction

Abstract: Aims Heart failure with preserved ejection fraction (HFpEF) is a heterogeneous syndrome with various causes that may influence prognosis. Methods and results We extracted the electronic medical records for 2180 consecutive patients hospitalized between 2016 and 2019 for decompensated heart failure. Using a text mining algorithm looking for a left ventricular ejection fraction ≥50% and plasma brain natriuretic peptide level >100 pg/mL, we identified 928 HFpEF patients. We screened for a prevailing cause of HFpE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 33 publications
0
23
0
2
Order By: Relevance
“…Previous studies reported that HFrEF of ischemic origin had higher mortality than HFrEF due to non-ischemic causes ( 25 , 26 ). A study exploring the prognosis in patients with HFpEF reported a specific phenogroup containing all patients with CAD had significantly different mortality compared with other phenogroups ( 27 ). However, our study revealed no significant differences in mortality between CAD and without CAD groups in HFrEF and HFpEF ( Supplementary Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that HFrEF of ischemic origin had higher mortality than HFrEF due to non-ischemic causes ( 25 , 26 ). A study exploring the prognosis in patients with HFpEF reported a specific phenogroup containing all patients with CAD had significantly different mortality compared with other phenogroups ( 27 ). However, our study revealed no significant differences in mortality between CAD and without CAD groups in HFrEF and HFpEF ( Supplementary Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Повысить качество и продолжительность жизни пациентов с ХСН можно с помощью этиотропной и патогенетической терапии. Персонифицированный подход к лечению прежде всего диктует необходимость учета этиологической неоднородности группы пациентов с ХСН [13][14][15]. Поскольку состояния, которые осложняются развитием сердечной недостаточности, различны по своему патогенезу, создание универсальных алгоритмов терапии затруднительно [11,14].…”
Section: общие принципы лечения сердечной недостаточностиunclassified
“…Studies have shown that heart failure manifests as progressive cardiomyocyte apoptosis, inflammatory response, interstitial fibrosis, and myocardial structural remodeling [ 5 ]. At present, there is no good way to delay and improve the occurrence and development of heart failure, so there are more and more studies on the occurrence, development, and prognosis of heart failure [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%